Prioritizing strategies for comprehensive liver cancer control in Asia: a conjoint analysis - Bridges John FP; Dong Liming; Gallego Gisselle; Blauvelt Barri M; Joy Susan M; Pawlik Timothy M (BMC, 2012)
Abstract Background Liver cancer is a complex and burdensome disease, with Asia accounting for 75% of known cases. Comprehensive cancer control requires the use of multiple strategies, but various stakeholders may have different views as to which strategies should have the highest priority. This study identified priorities across multiple strategies for comprehensive liver cancer control (CLCC) from the perspective of liver cancer clinical, policy, and advocacy stakeholders in China, Japan, South Korea and Taiwan. Concordance of priorities was assessed across the region and across respondent roles. Methods Priorities for CLCC were examined as part of a cross-sectional survey of liver cancer experts. Respondents completed several conjoint-analysis choice tasks to prioritize 11 strategies. In each task, respondents judged which of two competing CLCC plans, consisting of mutually exclusive and exhaustive subsets of the strategies, would have the greatest impact. The dependent variable was the chosen plan, which was then regressed on the strategies of different plans. The restricted least squares (RLS) method was utilized to compare aggregate and stratified models, and t-tests and Wald tests were used to test for significance and concordance, respectively. Results Eighty respondents (69.6%) were eligible and completed the survey. Their primary interests were hepatitis (26%), hepatocellular carcinoma (HCC) (58%), metastatic liver cancer (10%) and transplantation (6%). The most preferred strategies were monitoring at-risk populations (p<0.001), clinician education (p<0.001), and national guidelines (p<0.001). Most priorities were concordant across sites except for three strategies: transplantation infrastructure (p=0.009) was valued lower in China, measuring social burden (p=0.037) was valued higher in Taiwan, and national guidelines (p=0.025) was valued higher in China. Priorities did not differ across stakeholder groups (p=0.438). Conclusions Priorities for CLCC in Asia include monitoring at-risk populations, clinician education, national guidelines, multidisciplinary management, public awareness and centers of excellence. As most priorities are relatively concordant across the region, multilateral approaches to addressing comprehensive liver cancer would be beneficial. However, where priorities are discordant among sites, such as transplantation infrastructure, strategies should be tailored to local needs.